Vegetation Type Mapping in East Khasi Hills District (Meghalaya State, India) by Remote Sensing - Balakrishna Reddy, M.; Blah, Baiantimon (Indian Forester, 2011)
Though Shillong and adjoining regions have been favourite sites for collection of plant specimens ever since Hooker showcased to the world the unique biodiversity in Khasi-Jaintia hills there has been no systematic study of the diverse vegetation types occurring exclusively within the district. The terrain through its inaccessibility in several places poses a considerable challenge for an exhaustive vegetation type mapping exercise. IRS P6 LISS III imageries when fused with PAN data provided high resolution imagery capable of providing precise details towards detailed delineation of principal vegetation types occurring in East Khasi Hills district of Meghalaya. The present study has emerged as the first instance when remote sensing technique has been pressed to use for delineation types appearing exclusively within any particular district in Eastern Himalayas thereby settling the vexed issue of the actual vegetation types occurring in and around Shillong.